Structural Equation Modeling Multi-group of Science Process Skills and Cognitive in PjBL Integrated STEAM Learning - Anik Anekawati*; Jefri Nur Hidayat; Nabila Abdullah; Helliyatul Matlubah (Jurnal Pendidikan Sains Indonesia, 2021)
In Science, students tend to use the ability, which is dominantly controlled by their left-hemisphere brain. This study explores how science process skills (SPS) affect cognitive learning achievement (CLA) of dominantly right-brained and left-brained students. By applying project-based learning on the topic that integrates STEAM elements, this research examines the differences of the effects among those groups. The respondents were 32 8th-grade students from two randomly selected intact classes. This study employed a test to measure exogenous (SPS) and endogenous (CLA) latent variables. The partial least square - structural equation modeling (PLS-SEM) and multi-group PLS-SEM were employed to analyze the results. The evaluation of the outer model shows that both latent variables were valid and reliable. The factor loading value for all indicators of each latent variable was over 0.7. The cross-loading value indicates a higher correlation between the latent variable and its indicators compared to the other variables' indicators. The composite reliability and Cronbach's alpha values were over 0.7. The significance test shows that all indicators of each latent variable were valid. The evaluation of the inner model through the significance test (α=5%) suggests that the science process skill influenced CLA with a coefficient of 0.907. Meanwhile, the 0.822 R-square value demonstrates the variability of the SPS can explain the variability of CLA of 82.2%. The multi-group-SEM test reveals a difference in the effect of SPS toward CLA among dominantly right-brained and left-brained students. While the path coefficient for the former was 0.94, the latter was 0.881.